Role of herbal tea (camellia sinensis L. Kuntze, Zingiber officinale Roscoe and Morinda citrifolia L.) in lowering cholesterol level: a review and bibliometric analysis - Fadhlina, Anis; Alias, Nur Fatin Afifa; Sheikh Mohamed, Hassan Ibrahim; Zakaria, Nor Hafizah; Abdul Majid, Fadzilah Adibah; Hairani, Muhammad Afnan Shakir; Hudiyanti, Dwi (Elsevier B.V., 2023)
Dyslipidemia is defined as an imbalance level of lipids in the blood which is manifested by hypercholesterolemia and requires effective treatments or preventions. Numerous studies have discussed the various medicinal properties of Camellia sinensis, Zingiber officinale, and Morinda citrifolia, however, no bibliometric study about the trends and use of these three plants in cholesterol management around the world. Hence, this study employed the Scopus database to review the available literature on the potential cholesterol-lowering effects of these medicinal plants. In total, 822 articles were extracted, covering 360 keywords. Bibliometric analysis was done using VOSviewer software to analyse the global trends of the published articles focusing on the keywords, authors, countries, publication sources, and documents. The bioactive compounds, mechanisms of action, drug-herb interaction, and safe dosage were also addressed. The three plants were used globally in Asia, Africa, Europe, North America and South America. Z. officinale was the most researched plant, while India produced the highest number of documents. It was observed that these plants were scientifically proven in lowering the low-density lipoproteins cholesterol, triglycerides, and total cholesterol while increasing the high-density lipoproteins cholesterol due to their powerful bioactive constituents such as theaflavin, flavonol, gingerol, paradol, and niacin. Their major bioactive compounds have various mechanisms of action in altering lipid levels which require further studies to explore their mechanisms and benefits in a polyherbal form. Certain herbal-drug interactions and dosage should be taken into consideration to ensure the safe and effective usage of these plants. Our results hold significance for traditional and empirical medical evidence of this topic. More research collaborations are also needed to uncover research gaps such as molecular mechanisms, polyherbal formulations, and clinical trials. This will help in recognizing herbal medicine as a treatment approach for dyslipidemia.